2015
DOI: 10.1371/journal.pone.0142690
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Marine Bacterial Exopolysaccharide in Natural Marine Microbial Communities

Abstract: Most marine bacteria produce exopolysaccharides (EPS), and bacterial EPS represent an important source of dissolved organic carbon in marine ecosystems. It was proposed that bacterial EPS rich in uronic acid is resistant to mineralization by microbes and thus has a long residence time in global oceans. To confirm this hypothesis, bacterial EPS rich in galacturonic acid was isolated from Alteromonas sp. JL2810. The EPS was used to amend natural seawater to investigate the bioavailability of this EPS by native p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 57 publications
(64 reference statements)
1
46
0
Order By: Relevance
“…It was indicated that JL2810 EPS contained a large amount of GalA (42%) [32]. Similarly, it was indicated that the EPS produced by Alteromonas isolated from deep-sea hydrothermal vents also contained relatively large amount of acidic sugars such as GlcA and GalA [13,28,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…It was indicated that JL2810 EPS contained a large amount of GalA (42%) [32]. Similarly, it was indicated that the EPS produced by Alteromonas isolated from deep-sea hydrothermal vents also contained relatively large amount of acidic sugars such as GlcA and GalA [13,28,33,34].…”
Section: Resultsmentioning
confidence: 99%
“…However, phytoplankton is not the only source of polysaccharides, because bacteria exude polysaccharides themselves (Thornton, 2014;Zhang et al, 2015). Mostly, bacterial polysaccharides consist of mannose, rhamnose, glucose, galactose and galacturonic acid, and are characterized by their high proportion of uronic acid (20%-50%), which tend to form complexes with transition metals due to its negative charge (Zhang et al, 2015). Compared with phytoplankton polysaccharides, polysaccharides of bacterial origin have a higher resistence against mineralization by microbes and thus longer residence times.…”
Section: Acquisition Of Polysaccharides By Heterotrophic Bacteriamentioning
confidence: 99%
“…Compared with phytoplankton polysaccharides, polysaccharides of bacterial origin have a higher resistence against mineralization by microbes and thus longer residence times. Nevertheless, bacterial polysaccharides can also be utilized by dinstinct bacteria, which mostly belong to the Bacteroidetes (Zhang et al, 2015). Such secondary usage of polysaccharides (after the primary utilization of phytoplankton-derived polysaccharides) yields humic-like components that contribute to the formation of refractory DOC in the oceans.…”
Section: Acquisition Of Polysaccharides By Heterotrophic Bacteriamentioning
confidence: 99%
See 2 more Smart Citations